A Single Nucleotide Polymorphism Within Molybdenum Cofactor Sulfurase Gene Is Associated With Neuropsychiatric Conditions - Safa, Amin; Davood Omrani, Mir; Nicknafs, Fwad; Komaki, Alireza; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Molecular Biosciences, 2020)
Background: Molybdenum cofactor sulfurase (MOCOS) is an enzyme participating in purine metabolism. The aim of current study was to evaluate the role of a single nucleotide polymorphism (SNP) in the coding gene (rs594445) in mood disorders and methamphetamine addiction. Methods: This SNP was genotyped in 200 persons with methamphetamine addiction, 85 patients with bipolar disorder 1 (BP1), 78 patients with BP2, 33 patients with major depressive disorder (MDD) and 200 age-/ sex-matched normal subjects using the tetra-primer amplification-refractory mutation system (ARMS)-PCR technique. Results: The rs594445 was associated with methamphetamine addiction in co-dominant model (A/A vs. C/C: OR (95% CI)= 0.466 (0.252-0.864), P value=0.014; C/A vs. C/C: OR (95% CI)= 0.641 (0.418-0.981), P value=0.04). This SNP was also associated with this trait in dominant model (OR (95% CI)= 0.591 (0.398-0.879), P value=0.009). The A allele of rs594445 had a protective role against methamphetamine addiction (A vs. C: OR (95% CI)= 0.645 (0.48-0.866), P value=0.004). The rs594445 was associated with BP1 in co-dominant model (C/A vs. C/C: OR (95% CI)= 0.423 (0.230-0.778), P value=0.005). However, the associations were insignificant in other inheritance models. Conclusion: Finally, there were no significant associations between the mentioned SNP and risk of BP2 or MDD in any inheritance model. The present project highlights the role rs594445 in two psychiatric conditions and implies the presence of common genetic factors for these disorders.